2013
DOI: 10.1002/erv.2260
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Function in Patients with Anorexia Nervosa and Bulimia Nervosa

Abstract: The patients with eating disorders showed normal intellectual functions compared with the normative population. However, the AN group displayed a consistently lower performance than the matched HC group, which performed above normative means. The BN group performed at a level between that of the AN and HC groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 84 publications
2
17
0
Order By: Relevance
“…Recent studies also showed variable results. In a small study, borderline intelligence levels were seen in severe restricting‐type AN patients but Weider et al found average intelligence levels in AN patients but higher intelligence levels in BN patients (especially with respect to PIQ) shortly after admission to full‐time care. Kjaersdam Telleus et al found, in adolescent AN patients, FSIQ close to normal, but significantly worse PIQ compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies also showed variable results. In a small study, borderline intelligence levels were seen in severe restricting‐type AN patients but Weider et al found average intelligence levels in AN patients but higher intelligence levels in BN patients (especially with respect to PIQ) shortly after admission to full‐time care. Kjaersdam Telleus et al found, in adolescent AN patients, FSIQ close to normal, but significantly worse PIQ compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 96%
“…Despite this growing interest in (high) intelligence as a possible vulnerability marker for development of EDs, intelligence levels in ED patients are not extensively studied yet. A few studies and one systematic review, predominantly in anorexia nervosa (AN) patients, showed that intelligence levels are as high as, or probably higher than in the general population …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigating intelligence levels in anorexia nervosa [74,75] do not speak in favor of significantly reduced intelligence in anorexia nervosa. Furthermore, in our sample, there was no significant difference in the educational level between patients and healthy controls, making a significant difference in the intelligence level and thus a confounding effect on our results unlikely.…”
Section: Limitationsmentioning
confidence: 89%
“…Although this could be explained by the fact that the length of stay required by those patients is shorter, it could also be a result of a higher degree of cognitive impairment in those with lower weight at entry. Making early engagement with treatment in patients with cognitive difficulties may be more difficult as recent studies have demonstrated an association between cognitive function and low BMI (Chan et al, ; Weider, Indredavik, Lydersen, & Hestad, 2014). However, the relationship between BMI and cognitive functioning is complex, and our clinical impression is that some patients at low BMI still perform astonishingly well, for example, by continuing with their studies and work even at very low weights.…”
Section: Discussionmentioning
confidence: 99%